Is furcation involvement affected by adjunctive systemic amoxicillin plus metronidazole? A clinical trials exploratory subanalysis. (10th August 2016) - Eickholz, Peter; Nickles, Katrin; Koch, Raphael; Harks, Inga; Hoffmann, Thomas; Kim, Ti‐Sun; Kocher, Thomas; Meyle, Jörg; Kaner, Doğan; Schlagenhauf, Ulrich; Doering, Stephan; Gravemeier, Martina; et al.
Abstract: Objectives: Evaluation of the clinical effect of systemic amoxicillin and metronidazole adjunctively to mechanical debridement at furcation sites. Material and Methods: This is an exploratory per‐protocol collective subanalysis from a prospective, randomized, double‐blind, multi‐centre trial (ClinicalTrials.gov NCT00707369) on the effect of adjunctive systemic amoxicillin 500 mg plus metronidazole 400 mg (3×/day, 7 days) use on furcation involvement in moderate to severe periodontitis. Outcome was the change in frequency of classes of furcation involvement after 27.5 months. Therapy comprised mechanical debridement in conjunction with antibiotic or placebo administration, and maintenance therapy at three months intervals. Results: Three hundred and forty‐five patients (175 placebo, 170 antibiotics) with 6576 furcation sites (class 0 2956; class I 2370; class II 886; class III 364) were examined (3472 placebo, 3104 antibiotics). Pocket reduction/attachment gain at the furcation sites was noticeably better after antibiotics (1.2/0.6 mm) than after placebo (0.7/0.2 mm) 27.5 months after therapy. However, most furcation degrees were unchanged (placebo 61.5%/antibiotics 62.2%), more sites improved than deteriorated (20.3%/18.2%, 22.1%/15.7% respectively) and no differences in the change of furcation degrees between treatments could be detected. Conclusion: Compared to placebo, prescription of adjunctive systemic antibiotics failed to show clinically relevant benefit with regard to furcation class involvement.